Communicative competence in postmodern art (Al-Academy, 2024)
This study presents the concept of communicating as criticism analytical vision of art in general and contemporary composition particularly. Art is a means of communication for that activity to participate in the information or meanings, where the artwork is the message that includes what the artist sends ideas ,to the recipient . Thus, the language of communication between the artist and the receiver are made through the artwork (whatever his specialty: theatrically, plastic art, musically) and the magnitude of the meaning of outwardly or inwardly, is determined by the relationship between the artist and the recipient of which lead us turn to the issue of communication between them . .At that determined search through which we seek to monitor the communicative relationship between the artist and society by developments, and its relationship to the other from the other side in the post-modernism monitor . This art (the art of postmodernism) grew up with intellectual concepts group , Also associated the rapid changes that were the results of cultural interactions and mixing with the new technology in the second half of the twentieth century . Here comes the role of the artist, who must face this rapidly changing and overlapping change in his behavior towards his community and his artistic vision , Creatively new conditions disconnected with perceptions of idealism and metaphysics, and looking for legitimacy in a new reality advantage rapid development and multiplicity and overlap between the various areas of knowledge , To face the media and communication revolution, understand and critique what those witnessing contemporary societies of new phenomena have contributed to the creation of a radical change to the terms communication between artist and audience, and between the culture of another , Focusing on constituent bypass traditional forms to the world of culture and art, and invent a new style of art (in its mechanisms, and organized synthetic) in order to achieve his communicative mutual, In the context of these changes, start the research problem, raised by the question limited to: the way in which artist creates perceptions to create a renewable form of art, holds property communication among others, in a changing society and open-minded . As the importance of research in communication, do not come from being a Building for a society based on knowledge and communication, but also to support and attributed art in general (and postmodern art, in particular) critical thinking and systematic scientific and renewable values. To be the goal of this study is: finding efficiency communicative in art in general, the art of composition in particular, the detection of an artist's ability to transform the artwork of the structure of static to another open and open to the community, bringing elements of creativity and innovation and cash through communication. And will be studied through three sections: the first deals with incorporation philosophical continue, and the second section looks at the efficiency communicative in art, through three axes first (mind communicative), II (World Living) and third (levels of interaction between the receiver and the artwork), either the third sectioncontains a communicative activity and interactive context in postmodern art ..